Implementation of Islamic Education Values through 5S Habits: A Program Managemnet Approach in Madrasa - Khakim, Luthfi; Muthia, Ratna; Asiyah, Nur; Mahmudulhassan, Mahmudulhassan (QUALITY, 2025)
Amidst an ethical and moral crisis marked by rising bullying and social injustice, implementing character education through the 5S practice (Senyum, Salam, Salim, Sapa, Sopan) in madrasas is crucial to reinstilling Islamic educational values. This study aims to describe how the 5S fosters Islamic character in students at MI Al-Khoiriyyah 2 Semarang. This study is a descriptive qualitative field study. The subjects of the study were homeroom teachers and students who were selected based on their active involvement in implementing the 5S culture in the madrasa environment. Data were collected through observation, interviews, and documentation. Data validity strengthened through source and technique triangulation, member checks, and audit trails. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, presentation, and drawing conclusion. The results of the study indicate that the implementation of Islamic educational values that can be integrated into the 5S habituation at MI Al-Khoiriyyah 2 Semarang includes: rahmah (compassion), silaturrahmi, respect, strengthening ukhuwah (brotherhood), tawadhu’ (obedience), and social concern. Supporting factors for implementing the 5S habituation at MI Al-Khoiriyyah 2 Semarang include the learning environment, community environment, and family environment. This study contributes to the literature by demonstrating how the 5S habituation can effectively integrate Islamic moral values into educational practices. It also provides madrasas with a practical reference for strengthening positive cultures and teacher role models.